Atypical CML with TET2 mutation, associated with NRAS and KRAS: A case report and literature review. (November 2021) - Abuzneid, Yousef S.; Alzeerelhouseini, Hussam I.A.; Marzouqa, Nizar; Yaghi, Yasmine; Al-Ihribat, Alaa R.; Alqam, Bilal; Krama, Akram
Abstract: Background: Atypical chronic myeloid leukemia ( BCR-ABL1 negative) is a rare myeloid neoplasm with poor prognosis and no current standard of treatment. It features both myelodysplastic and myeloproliferative characteristics with little data regarding mutations playing a role in the disease. Presentation of case: We present a case of a 55-year-old female complaining of fever, cough, general weakness and night sweats. Examinations showed leukocytosis with a left shift, thrombocytopenia, hypercellular bone marrow with marked granulocytic hyperplasia and a negative BCR-ABL. After ruling out myelodysplastic and other myeloproliferative diseases the patient was finally diagnosed as aCML according to the WHO criteria with mutations in the TET2 gene, the NRAS gene and in the KRAS gene. The patient was started on Hydroxyurea for a duration of 9 months with an excellent initial response leading to normalization of her platelets and WBCs. However, in the last month she stopped responding to therapy and her state of health started declining once again. Conclusion: Atypical chronic myeloid leukemia ( BCR-ABL1 negative with presence of TET2 gene mutation) is an unusual finding in myeloid neoplasms, have unknown prognosis and no current standard of treatment. It features both myelodysplastic and myeloproliferative characteristics with little data regarding mutations playing a role in the disease. Highlights: Atypical CML is challenging to diagnose and can be misdiagnosed with CMML. Careful history taking, meticulous physical examination, and investigations are necessary. A treatment is not yet stipulated; however, researchers are working on it.